Tokunbo and chinco economies in Nigeria: rethinking encounters and continuities in local economic transformations (2015)
As encounters and interactions of Nigeria with Western and Asian economic powers intensify and deepen, the Nigerian economy continues to undergo transformations. This paper explores and compares Tokunbo and Chinco economies in this transformation process. As products of processes and patterns of incorporation of Nigeria into the world-economy, Tokunbo refers to an economy that relies on trade in second-hand, imported goods from the West while the Chinco economy is a recent creation through the influx of cheap China-made goods. They are parallel economies existing alongside, but mostly dominating, the local economy whose capabilities have been largely eroded as a result of decades of being in a protracted static position as a periphery nation. Their emergence is intricately connected to the overpowering juggernaut of global capitalism and the opportunistic tendencies and resolve of local entrepreneurs and transnational traders to participate in, as well as benefit from, the deepening incorporation of local market into the world-system, even if it means doing so as low-end actors. Also, while they are characteristically distinguishable, their logic and destabilising consequences are the same in a periphery nation. This calls for a rethink and critical reflection on the value of transnational processes which is currently intensifying in the face of global systems expansion, particularly the sort of trans-nationalism that is being facilitated by China’s interest in African countries.